Efficiency evaluation and experimental verification of the programme aimed at correcting schoolchildren’ psycho-physical condition using sports orienteering - GALAN, YAROSLAV; YACHNIUK, MAXYM; MOLDOVAN, ANDRIY; KYSELYTSIA, OKSANA; KOSTASHCHUK, OKSANA; BILENKOVA, LIDIIA; KANIVETS, TETIANA; FESUN, HALYNA; HAVRYLYUK, LIDIYA; BESHLEI, OLGA (My University, 2022)
Today, many studies prove the fact that learning in the modern school is a multifaceted phenomenon, as this process is marked by the cognitive ability of learners to perceive and process large amounts of information in a short period. The article aimed to study the impact of a comprehensive programme on sports orienteering on the psychophysical condition of schoolchildren aged 13-14 and experimentally test its effectiveness. Material and methods: Theoretical analysis, pedagogical, sociological, anthropometric, physiological, psychophysiological techniques, health assessment and statistical methods. Results: The results demonstrated a positive dynamic of most of the research indicators. The results showed that after conducting the pedagogical experiment the dynamics of average results of the girls and boys in experimental group (EG) were significantly higher than the ones showed by the boys and girls in the control group (CG) a. Conclusions: Thus, the positive changes in the indicators of the psychophysical condition of learners prove the effectiveness of the proposed programme.
Keywords: Orienteering, Schoolchildren, Psychological Condition, Physical Development, Fitness.